Extended π-conjugated ruthenium zinc–porphyrin complexes with enhanced nonlinear-optical properties. Issue 14 (12th January 2015) - de Torres, Miriam; Semin, Sergey; Razdolski, Ilya; Xu, Jialiang; Elemans, Johannes A. A. W.; Rasing, Theo; Rowan, Alan E.; Nolte, Roeland J. M.
Abstract : Zinc porphyrin dimers and trimers, in which the porphyrins are connected via a ruthenium metal core, exhibit large third-order nonlinear optical absorption coefficients and refractive indices. Abstract : Zinc porphyrin dimers and trimers, in which the porphyrins are connected via a ruthenium metal core, exhibit large third-order nonlinear optical absorption coefficients and refractive indices. These properties are a result of the presence of multiple porphyrins, which lead to an extension of the π-conjugated system and the octupolar effect.